Ecological Relationships Between Woody Species Diversity and Propagation Strategies of Aulonemia queko - Hugo Cedillo; Luis G. García-Montero; Fernando Bermúdez; Andrés Arciniegas; Mélida Rocano; Oswaldo Jadán (Plants)
This study explores how floristic composition, diversity, and woody vegetation structure vary across floristic zones in Andean montane forests under the dominance of Aulonemia queko Goudot (Poaceae, Bambusoideae) dominance. As a culturally and ecologically significant non-timber forest product, A. queko plays a key role in shaping plant communities and requires effective propagation strategies for sustainable management. Significant differences in floristic composition were observed among zones, with indicator species identified in the lower and upper zones. However, despite environmental variability, species richness and structural attributes remained stable across the elevation gradient, suggesting resilience in woody plant communities. A. queko density was highest in the upper zone, while its basal area peaked in the lower and middle zones, probably shaping floristic composition through competitive interactions and habitat modification. Propagation experiments revealed that shoots with rhizomes exhibited higher survival and growth, particularly in mulch substrates with 1000 ppm indole-3-butyric acid (IBA), highlighting the importance of shoot type, substrate, and hormone dose. These findings suggest that A. queko is a structuring species and a potential restoration target. However, its dominance may alter forest composition, requiring adaptive management strategies that balance its ecological role with conservation and sustainable use, ensuring biodiversity and ecosystem resilience.